Buffer-mediated activation of Candida antarctica lipase B dissolved in hydroxyl-functionalized ionic liquids - Ou, Guangnan（Jimei Univ, Sch Bioengn）; Yang, Jing; He, Biyan（Jimei Univ, Sch Bioengn）; Yuan, Youzhu; 袁友珠 (Journal of Molecular Catalysis B: Enzymatic, 2010)
Ionic-liquid buffer having phosphate anion was synthesized for the development of buffered enzymatic ionic liquid systems Both the conformation and transesterification activity of Candida antarctica lipase B (CALB) dissolved in the hydroxyl-functionalized ionic liquids were buffer dependent Intrinsic fluorescence studies indicated that the CALB possessed a more compact conformation in the medium consisted of ionic liquid buffer having phosphate anion and hydroxyl-functionalized ionic liquids like 1-(1-hydroxyethyl)-3-methyl-imidazolium tetrafluoroborate and 1-(1-hydroxyethyl)-3-methyl-imidazolium nitrate High activity and outstanding stability could be obtained with the CALB enzyme in the buffered ionic liquids for the transesterification (c) 2010 Elsevier B V All rights reserved NSFC[20873108, 20923004]; Science Foundation of Jimei University[2009CB939804]; Key Scientific Project of Fujian Province[2009HZ0002-1]